Women’s Improvements in Cardiorespiratory Fitness Following Cardiac Rehabilitation Differ by Body Mass Index Category - Heather E. Conradson, RN, PhD; Daniele Chirico, PhD; Kathryn King-Shier, RN, PhD, FESC; Codie Rouleau, RPsych PhD; Tavis S. Campbell, PhD; Sandeep Aggarwal, MD, FRCPC; Ross Arena, PhD; Trina Hauer, MSc; Stephen B. Wilton, MD, MSc; Tamara M. Williamson, PhD (CJC Open)
Background: Improving women’s cardiovascular outcomes requires optimizing cardiorespiratory fitness (CRF), as higher CRF predicts improved mortality in people with cardiovascular disease (CVD). As such, increasing CRF is a key goal of cardiac rehabilitation (CR). This study assesses the potential influence of body habitus, assessed by body mass index (BMI), on improvements in CRF in women with CVD. Methods: Women (18+ years) diagnosed with CVD who completed a 12-week exercise-based CR program between 1996 and 2016 were included in this retrospective analysis. Women completed a symptom-limited graded exercise test before CR and at CR completion to determine CRF via peak metabolic equivalents (METs). Women were categorized by baseline BMI: normal = 18.5 to 24.9 kg/m2, overweight = 25.0 to 29.9 kg/m2, and obese ≥ 30 kg/m2. Mixed analysis of covariance (ANCOVA) was performed to evaluate the impact of BMI classification on ΔMETs at 12 weeks. Results: Data from 1313 women (mean age = 62 ± 11 years) were analyzed. Results from mixed ANCOVA indicated a significant time (pre-CR, 12 weeks) by BMI category interaction (F [2,1307] = 3.20, P = 0.041, ƞp2 = 0.005). Follow-up analyses of variance (ANOVAs) showed significant improvements in ΔMETs in women with normal and overweight BMI categories (standard mean difference =1.03, n = 454 and 0.92, n = 461, respectively, P < 0.001). However, ΔMETs among women classified as obese was nonsignificant using a Bonferroni-adjusted alpha of 0.017 (standardized mean difference [SMD] = 0.79, P = 0.028; n = 398). Conclusions: A 12-week exercise-based CR program increased CRF in women classified as normal or overweight by BMI, whereas those with obesity did not realize similar improvements. Women with obesity may need tailored strategies to increase their improvements in CRF in CR. Clinical Trial Registration: REB18-0083. Résumé: Contexte: L'amélioration des pronostics cardiovasculaires chez les femmes passe par l'optimisation de la condition cardiorespiratoire (CCR), car une CCR élevée est prédictive d'une mortalité réduite chez les personnes atteintes de maladie cardiovasculaire (MCV). L'amélioration de la CCR est donc un objectif clé de la réadaptation cardiaque (RC). Cette étude évalue l'influence potentielle de la constitution physique, évaluée par l'indice de masse corporelle (IMC), sur l'amélioration de la CCR chez les femmes atteintes de MCV. Méthodes: Les femmes (18 ans et plus) diagnostiquées avec une MCV qui ont suivi un programme de RC basé sur l'exercice physique durant 12 semaines, entre 1996 et 2016, ont été incluses dans cette analyse rétrospective. Les femmes ont effectué un test d'exercice gradué limité par les symptômes, avant la RC et à la fin de la RC, pour déterminer la CCR par le biais d'équivalents métaboliques (MET) maximaux. Les femmes ont été classées en fonction de leur IMC de base: normal = 18,5 à 24,9 kg/m2, surpoids = 25,0 à 29,9 kg/m2, et obésité ≥ 30 kg/m2. Une analyse mixte de la covariance (ANCOVA) a été réalisée pour évaluer l'impact de la classification de l'IMC sur les ΔMET à 12 semaines. Résultats: Les données de 1 313 femmes (âge moyen = 62 ± 11 ans) ont été analysées. Les résultats de l'ANCOVA mixte ont indiqué une interaction significative entre le temps (avant la RC, 12 semaines) et la catégorie d'IMC (ratio F [2,1307] = 3.20, p = 0,041, taille de l'effet ƞp2 = 0,005). Les analyses de variance (ANOVA) de suivi ont montré des améliorations significatives des ΔMET chez les femmes ayant un IMC normal ou en surpoids (différence moyenne standard = 1,03, n = 454 et 0,92, n = 461, respectivement, p < 0.001). Cependant, chez les femmes classées comme obèses, les ΔMET n'étaient pas statistiquement significatives en utilisant une valeur alpha ajustée de Bonferroni de 0,017 (différence moyenne standardisée = 0,79, p = 0,028, n = 398). Conclusions: Un programme de RC de 12 semaines basé sur l'exercice physique a augmenté la CCR chez les femmes classées comme normales ou en surpoids selon leur IMC, alors que celles souffrant d'obésité n'ont pas obtenu d'améliorations similaires. Les femmes souffrant d'obésité pourraient avoir besoin de stratégies adaptées pour améliorer leur CCR dans le cadre d'un programme de RC. Numéro d'enregistrement de l'essai clinique: REB18-0083.